Sources of Islamic Family Law: A Comparative Study of Classical and Contemporary Interpretations - Lalu Kesa Rahmatullah; Ikrima Fajri Agustina Yusuf (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
The purpose of this study is to compare classical and contemporary interpretation methods as sources of Islamic family law. The main problem of this paper is how the approach used by classical and contemporary interpretation, what are the differences between the two methods, and the relevance of both as references for Islamic family law. This study uses a qualitative approach with a literature study to gather in-depth information on the theme. The results of the study indicate that the classical interpretation method is textual in nature and maintains the originality of the verses, while the contemporary method provides many new approaches that are more relevant to the present day. The differences between the two lie in the period of emergence, sources, approaches, and the main methods used in interpreting the verses. Both are relevant in addressing the challenges of Islamic family law sources, the classical method as the initial foundation and developed with various approaches by the contemporary method to become a foundation for society in the modern era